So u have to add all the sides up.
which will give you 6 + 6√3 + 6 +6√3
because their opposite and parallel lengths and widths are equal
that gives you 12 + 12√3
so ans is 12m + 12√3m
Answer:
x = 8/3
Step-by-step explanation:
(When solving for a variable, always do the opposite of PEMDAS)
-5 + 4 = 3x - 9
-1 = 3x - 9
8 = 3x
8/3 = x
SUM OF ANGLES IN A TRIANGLE THEOREM (SATT)
Answer:
See below
Step-by-step explanation:
![\tan A+\tan B + \tan A.\tan B = 1\\\\ \implies \: \tan A + \tan B = 1 - \tan A.\tan B \\ \\ \implies \: \frac{\tan A + \tan B}{ 1 - \tan A.\tan B } = 1\\ \\ \implies \: \tan (A + B) = 1 \\ \\ \implies \: \tan (A + B) =\tan 45 \degree \\ \\ \implies \: A + B = 45 \degree \\ \\ thus \: proved](https://tex.z-dn.net/?f=%5Ctan%20A%2B%5Ctan%20B%20%2B%20%5Ctan%20A.%5Ctan%20B%20%3D%201%5C%5C%5C%5C%20%5Cimplies%20%5C%3A%20%5Ctan%20A%20%2B%20%20%5Ctan%20B%20%3D%20%201%20-%20%20%5Ctan%20A.%5Ctan%20B%20%20%5C%5C%20%20%5C%5C%20%5Cimplies%20%5C%3A%20%20%5Cfrac%7B%5Ctan%20A%20%2B%20%20%5Ctan%20B%7D%7B%201%20-%20%20%5Ctan%20A.%5Ctan%20B%20%7D%20%3D%201%5C%5C%20%20%5C%5C%20%5Cimplies%20%5C%3A%20%20%5Ctan%20%28A%20%2B%20%20B%29%20%3D%201%20%5C%5C%20%20%5C%5C%20%5Cimplies%20%5C%3A%20%20%5Ctan%20%28A%20%2B%20%20B%29%20%3D%5Ctan%2045%20%5Cdegree%20%5C%5C%20%20%5C%5C%20%5Cimplies%20%5C%3A%20%20A%20%2B%20%20B%20%3D%2045%20%5Cdegree%20%5C%5C%20%20%5C%5C%20%20thus%20%5C%3A%20proved)
Answer:
<u>y+5 =-3</u>
x-1
y+5=-3x +3
y=-3x-2
Step-by-step explanation: